Increased levels of circulating and tumor-infiltrating granulocytic myeloid cells in colorectal cancer patients - Toor, Salman M.; Syed Khaja, Azharuddin Sajid; El Salhat, Haytham; Bekdache, Omar; Kanbar, Jihad; Jaloudi, Mohammed; Elkord, Eyad (Frontiers in Immunology, 2016)
Increased levels of myeloid cells, especially myeloid-derived suppressor cells (MDSCs), have been reported to correlate with bad prognosis and reduced survival in cancer patients. However, limited data are available on their conclusive phenotypes and their correlation with clinical settings. The aim of this study was to investigate levels and phenotype of myeloid cells in peripheral blood and tumor microenvironment of colorectal cancer (CRC) patients, compared to blood from healthy donors (HDs) and paired, adjacent non-tumor colon tissue. Flow cytometric analysis was performed to examine the expression of different myeloid markers in fresh peripheral blood samples from CRC patients and HDs, and tissue-infiltrating immune cells from CRC patients. We found significantly higher levels of cells expressing myeloid markers and lacking the expression of MHC class II molecule HLA-DR in blood and tumor of CRC patients. Further analysis revealed that these cells were granulocytic and expressed Arginase 1 (ARG1), indicative of their suppressive phenotype. These expanded cells could be neutrophils or granulocytic MDSCs, and we refer to them as granulocytic myeloid cells (GMCs) due to the phenotypical and functional overlap between these cell subsets. Interestingly, the expansion of peripheral GMCs correlated with higher stage and histological grade of cancer, thereby suggesting their role in cancer progression. Furthermore, an increase in CD33+CD11b+HLA-DR-CD14-CD15- immature myeloid cells (IMCs) was also observed in CRC tumor tissue. Our work shows that GMCs are expanded in circulation and tumor microenvironment of CRC patients, which provides further insights for developing immunotherapeutic approaches targeting these cell subsets to enhance anti-tumor immune and clinical responses.